2015
DOI: 10.3354/meps11388
|View full text |Cite
|
Sign up to set email alerts
|

Foraging ecology during nesting influences body size in a pursuit-diving seabird

Abstract: Causes and consequences of differences in seabird foraging strategies between breeding colonies are not well understood. We tested whether body size of a pursuit-diving seabird, the thick-billed murre Uria lomvia, differs between breeding colonies and, if so, how size differences can be understood in the context of differences in foraging behavior, habitat use, and breeding performance. We measured adult murres over 3 seasons (2008 to 2010) at 2 of the Pribilof Islands, St. Paul and St. George, located on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 67 publications
2
25
0
Order By: Relevance
“…, Paredes et al. ). Furthermore, tracking data record the presence of animals but not their absence (Aarts et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Paredes et al. ). Furthermore, tracking data record the presence of animals but not their absence (Aarts et al.…”
Section: Introductionmentioning
confidence: 98%
“…This is partly because tracking data violate many of the assumptions inherent to conventional parametric models (reviewed by Turchin 1998, Aarts et al 2008, Wakefield et al 2009). Repeat observations on individuals (typically 10 2 -10 4 locations/individual in seabird studies) tend to be spatiotemporally autocorrelated and the movements of individuals drawn from the same colony may be dependent on one another due to public information transfer and cultural and genetic divergence (Wakefield et al 2013, Paredes et al 2015. Furthermore, tracking data record the presence of animals but not their absence (Aarts et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that body size may play an important role in shaping the foraging decisions of murres breeding on the same colonies (Paredes et al. ). For instance, largeā€bodied individuals (such as daytime diving TBMU; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TBMU populations exhibit various behavioral patterns, which may be due to interregional differences in morphology . TBMUs from St. Paul Island with larger body mass and wing loading performed shorter foraging trips and deeper dives, whereas TBMUs from St. George Island with smaller body mass and wing loading performed longer foraging trips and shallower dives Paredes et al, 2015). Thus, segregation patterns between COMUs and TBMUs may differ among regions partly because their morphology differs at a regional scale.…”
Section: Discussionmentioning
confidence: 92%
“…A few studies have revealed inter-or intraspecific differences in the foraging behavior of COMUs and TBMUs from the aspects of morphology and breeding ecology (Barger et al, 2016). Paredes et al (2015) showed that, within TBMU colonies, smaller individuals tended to fly longer distances and dive shallower, whereas the opposite pattern was observed in larger individuals, likely reflecting their body mass and wing loading. TBMUs have also shown intersexual differences in the diel patterns of diving behavior (Jones et al, 2002;Paredes et al, 2008); however, the presence of such habitat partitioning appears to vary by geographical region (Elliott et al, 2010).…”
Section: Introductionmentioning
confidence: 99%